Loss of Drosophila NUS1 results in cholesterol accumulation and Parkinson's disease-related neurodegeneration. - Xue, J.; Zhu, Y.; Wei, L.; Huang, H.; Li, G.; Huang, W.; Zhu, H.; Duan, R. (FASEB Journal (Federation of American Societies for Experimental Biology), 2022)
NgBR is the Nogo-B receptor, encoded by NUS1 gene. As NgBR contains a C-terminal domain that is similar to cis-isoprenyltransferase (cis-IPTase), NgBR was speculated to stabilize nascent Niemann-Pick type C 2 (NPC2) to facilitate cholesterol transport out of lysosomes. Mutations in the NUS1 were known as risk factors for Parkinson's disease (PD). In our previous study, it was shown that knockdown of Drosophila NUS1 orthologous gene tango14 causes decreased climbing ability, loss of dopaminergic neurons, and decreased dopamine contents. In this study, tango14 mutant flies were generated with a mutation in the C-terminal enzyme activity region using CRISPR/Cas9. Tango14 mutant showed a reduced lifespan with locomotive defects and cholesterol accumulation in Malpighian tubules and brains, especially in dopaminergic neurons. Multilamellar bodies were found in tango14 mutants using electron microscopy. Neurodegenerative-related brain vacuolization was also detected in tango14 knockdown flies in an age-dependent manner. In addition, tango14 knockdown increased ?-synuclein (?-syn) neurotoxicity in ?-syn-overexpressing flies, with decreased locomotive activities, dopamine contents, and the numbers of dopaminergic neurons in aging flies. Thus, these observations suggest a role of NUS1, the ortholog of tango14, in PD-related pathogenesis.